1986
DOI: 10.1152/ajpregu.1986.251.3.r525
|View full text |Cite
|
Sign up to set email alerts
|

Pressor resistance to vasopressin in sodium depletion, potassium depletion, and cirrhosis

Abstract: Resistance to the pressor effects of angiotensin II, but not norepinephrine, has been observed in sodium depletion, potassium depletion, and cirrhosis. We tested the response to arginine vasopressin (AVP) in each of these conditions. Male Sprague-Dawley rats were made sodium depleted with furosemide and a low-sodium diet for 3 days, potassium depleted by feeding a low-potassium diet for 14-21 days, or cirrhotic by inhalation of carbon tetrachloride for 8 wk. In conscious rats, the pressor response to graded do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
1

Year Published

1991
1991
2003
2003

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 0 publications
2
15
1
Order By: Relevance
“…In our study, the hyporesponsiveness to methoxamine could be demonstrated only by the response in total peripheral resistance but not MAP. The failure to demonstrate a hyporesponsiveness to vasoconstrictors in terms of changes in MAP was also observed in a previous study by Murray and Paller (4,5) in cirrhotic rats. These authors estimated vascular sensitivity by only examining the pressure response, which is less sensitive than measurements of changes in vascular resistance that we performed in our study.…”
Section: Discussionsupporting
confidence: 78%
“…In our study, the hyporesponsiveness to methoxamine could be demonstrated only by the response in total peripheral resistance but not MAP. The failure to demonstrate a hyporesponsiveness to vasoconstrictors in terms of changes in MAP was also observed in a previous study by Murray and Paller (4,5) in cirrhotic rats. These authors estimated vascular sensitivity by only examining the pressure response, which is less sensitive than measurements of changes in vascular resistance that we performed in our study.…”
Section: Discussionsupporting
confidence: 78%
“…BP was not significantly different between LC and NC at week 4, but LC had lower BP ( Figure 7) and heart rate (310 Ϯ 11 versus 360 Ϯ 7; P Ͻ 0.05) than NC at week 8 as previously reported (21,22). ETA blockade had no significant effect on BP in normal K ϩ and K ϩ -deficient rats.…”
Section: Etb Blockade Induced Hypertension In Normal Ksupporting
confidence: 76%
“…If this mechanism occurs in normokalemic animals, then endothelial dysfunction induced by hypokalemia may also contribute to the lack of BP elevation in hypokalemic rats administered the ETB antagonist. In addition, Murray et al (21) reported that the systemic vasculature is resistant to the pressor effect of AngII and vasopressin in chronic hypokalemia. Such pressor resistance to vasoconstrictors may also contribute to the absence of BP elevation in hypokalemic rats with ETB inhibition.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, in portal-veinligated rats, different laboratories have found that the mesenteric vessels show a hyporesponsiveness to vasoconstrictors [4,[7][8][9], but several papers agree that the aorta shows a normal response [23]. However, in cirrhotic rats with ascites, hyporesponsiveness to vasoconstrictors has been found in several vessel types [6,8,[24][25][26][27].…”
Section: Discussionmentioning
confidence: 99%